Práticas pedagógicas em movimento na inclusão escolar - Braga, Isabel Cristina Alves Pimenta (2016)
This article presents my pedagogical proposal for the teaching of art to students with disabilities, having the floor as a mobilizing element. It begins with a reflection on the initial formation, the continued formation and the pedagogical praxis, indicating the search for pedagogical paths in visual arts and in art therapy. I show the construction of artistic practices, with the presentation of a bodywork process involving students with disabilities, in a process that mobilizes the power of movement in bodies active for learning in art. The practice is thought of in my professional / personal trajectory and contextualized in art education, special education and inclusive school, through close relation ship with experience, autobiography and body sensitization. The focus of the propositions is on the activity with students with disabilities in the scope of corporal expression. Reflexive analysis is anchored by research on expressive body movement in studies related to the teaching of art and to the field of art therapy and somatic education. I present a descriptive and reflective memorial about teacher education in pedagogical practices in the context of art teaching and inclusive education. The procedures developed in the workshops with the group of students with disabilities is analysis based on the experiences of enhancement of the movement through the awareness of the body within the body expression. Finally, I theoretically emphasized the ground as one of the mobilizing body elements to potentiate the body's expressive movement articulated in practices with the students in otherness.